Patient perspectives on online medication information seeking in Uganda: a cross-sectional exploration - Nalugwa, Harima; S. Abd. Aziz, Madihah; Mahdi, Ghulam; Shah, Asadullah (IEEE, 2023)
This study explores pharmacists’ experiences and attitudes towards online medical information shared with them by their patients. A self-administered online survey questionnaire was designed and administered to 113 pharmacists within Kampala metropolitan, Uganda. The survey results highlight growth in patients’ inquiries about online acquired medication-related information from their pharmacists (n=105, 93%). Pharmacists highlighted that this online information-seeking behaviour enhances patients’ understanding of treatment. While generally, pharmacists in Uganda hold a positive attitude towards this trend, they, however, raised some concerns over the inaccuracy of online medication-related information presented to them by their patients 66 (58%), the internet promotion of unnecessary fear and worry about medication n=96 (92%), and the tendency for patients to take up more of the pharmacists’ time during their visits (n=68, 60%). Finally, this study revealed that pharmacist gender (r=0.722, t=9.078, p=0.000) and pharmacy ownership status (r=0.504, t=4.107, p=0.000) had a statistically significant relationship with pharmacists’ attitude towards patients’ acquisition of online medication-related information. Conclusively, this study shows that pharmacists in Kampala (Uganda) have a generally positive view of the online medication-related information-seeking by patients. This result suggests that technology use, specifically the Internet, in addressing healthcare needs is embraced in Sub-Saharan Africa. Therefore, this research contributes to the literature exploring online perceptions and attitudes towards medication related information-seeking among pharmacists.